Catch Shiny Droplets in Suspension—Finding the Needle in a Haystack. Issue 7 (20th July 2017) - Hein-Fuchs, Nina V.; König, Renate
Abstract : In a recent issue of Cell Chemical Biology, Chaipan et al. (2017) described a high-throughput screening methodology to identify epitopes on HIV-1 particles recognized by broadly neutralizing antibodies. The approach utilizes a droplet-based microfluidics platform combining robust phenotypic single-virus sorting with next-generation sequencing of viral quasispecies. Abstract : In a recent issue of Cell Chemical Biology, Chaipan et al. (2017) described a high-throughput screening methodology to identify epitopes on HIV-1 particles recognized by broadly neutralizing antibodies. The approach utilizes a droplet-based microfluidics platform combining robust phenotypic single-virus sorting with next-generation sequencing of viral quasispecies.